Kesan penularan wabak Covid-19 terhadap sektor perumahan dari perspektif kemampuan pemilikan rumah - Rameli, Norizan; Halim, Hasliana; Rahman, Riki (Penerbit UTHM, 2020)
Rumah menjadi hak setiap individu seperti termaktub dalam Universal Declaration of Human Rights 1948 : Everyone has a right to a standard of living adequate for the health and well-being of himself and of his family, including food, clothing, housing and medical care and necessary social services and the right to security in the event of unemployment, sickness, disability, widowhood, old age or the lack of livelihood in circumstances beyond his control. (United Nations, 1948) Kemampuan perumahan menjadi agenda penting bagi majoriti negara di peringkat global. Keperluan manusia untuk mempunyai rumah sebagai keperluan asas yang perlu dipenuhi meletakkan isu kemampuan perumahan sentiada diberi tumpuan dan dibahaskan sepanjang tahun...